2018
DOI: 10.1021/acs.inorgchem.8b00705
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Investigation into Luminescent Properties of Ir(III) Complexes: An Integrated Computational Study of Radiative and Nonradiative Decay Processes

Abstract: A comprehensive and concrete exploration into the deactivation mechanisms of luminescent materials is imperative, with the improvement of simulating and computing technology. In this study, an integrated calculation scheme is employed on five Ir(III) complexes for thorough investigation of their photophysical properties, including radiative ( k) and nonradiative ( k) decay rates. As a most famous Ir(III) complex with superior quantum efficiency, fac-Ir(ppy) herein serves as a reference relative to the other fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…The relevant chemistry is very well developed, numerous phosphorescent iridium complexes have been prepared and their photophysics was studied in detail experimentally and theoretically. [1,9,17,23,24,26,27] The complexes containing β-diketonate ligands as L^L chelates are an important part of this family of emitters. [5,[28][29][30][31][32] These type of compounds differ from the other complexes containing neutral chelates (for example, aromatic diimines) by zero complex charge and stronger (covalent/electrostatic) binding to metal center.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant chemistry is very well developed, numerous phosphorescent iridium complexes have been prepared and their photophysics was studied in detail experimentally and theoretically. [1,9,17,23,24,26,27] The complexes containing β-diketonate ligands as L^L chelates are an important part of this family of emitters. [5,[28][29][30][31][32] These type of compounds differ from the other complexes containing neutral chelates (for example, aromatic diimines) by zero complex charge and stronger (covalent/electrostatic) binding to metal center.…”
Section: Introductionmentioning
confidence: 99%
“…This photophysical profile strongly contrasts with the Φ PL and Φ PL of fac ‐Ir(dFppy) 3 ( τ PL = 1.64 µs, Φ PL = 77 %) . Indeed, previous DFT calculations for 1 suggested that the emission had MLCT mixed with intraligand charge transfer (ILCT) character and the poor emissive properties in solution were caused by efficient non‐radiative decay promoted by strong vibrations of the dbm in the low frequency region . Therefore, comparable behavior would be expected for complex 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Via variation of the main ligands, the emission colors for complexes Ir1-Ir7 can be adjusted from blue to yellow in CH 2 Cl 2 solutions. It is known that the control of the optical physical process must ensure the structural similarity, so that the expected increase of the radiative decay rate can ensure the improvement of the overall efficiency [22,23]. Hence, on the basis of complex Ir6 [21], we have theoretically designed four complexes and investigated their electronic structure and photophysical properties by density functional theory (DFT) and time-dependent density functional theory (TDDFT) method.…”
Section: Introductionmentioning
confidence: 99%